A Digital Therapeutic Communication Model to Improve Treatment Compliance of Hypertension Patients at Ubud Health Center 1 Gianyar District, Bali Province - Purnawan, I Nyoman; Suarjana, Nyoman; Kurniati, Ni Made (Sean Institute, 2022)
The main problem in controlling hypertension in Indonesia is low adherence to treatment hypertension patient. An important effort that is currently being done is to change patient behavior to be more compliant with treatment. Factors that influence medication adherence. It is important that it is studied in full, compiled on a strong theoretical basis and proven scientifically empirical. One of the factors that play an important role in increasing success. Treatment is therapeutic communication between health workers and patients. However, during the syndemy (synergy and pandemic) period of covid-19 with restrictions on interaction hinder the process of therapeutic communication so that there is a need for digital transformation. For Therefore, this study aims to assess the factors of medication adherence, compile and prove digital therapeutic communication models can improve adherence to treatment of hypertensive patients at Ubud Health Center 1, Gianyar Regency, Bali Province. Research implementation consists of 3 stages, namely: 1) Research cross-sectional study with a sample size of 390 hypertensive patients selected by simple random sampling. Data collected by interview using structured questionnaires in selected patient homes; 2) Modeling digital therapeutic communication and 3) Proof of models with quasi-experimental designs using a cluster randomized controlled trial design. Structural equation modelling (SEM) was used for factor analysis of medication adherence and the Poisson regression test was used to test and assess the capabilities of digital therapeutic communication models for improve adherence to treatment of hypertensive patients. Factors that are proven to improve adherence to treatment is a type of communicator (β=0.297), content of the message conveyed (β=0.237) and the type of digital media (whatsapp) used (β=0.443). Therapeutic communication model. Digital is proven to increase medication adherence by 4.1 times (95% CI: 0.845-11.557). It can be concluded that therapeutic communication with WhatsApp media is very effective carried out supported by the ability of the communicator and the content of the message conveyed.